Flouting Maxim Found in WhatsApp Group Chat: Pragmatics Analysis: English - Angesthi Cipta Wening; Yuliyanto Sabat; Yudy Prasetyo (Prodi Tadris Bahasa Inggris, 2024)
The Gricean Maxim provides a framework for understanding and analyzing communicative interactions, offering insights into the dynamics of effective communication and cooperation in various contexts. This study is to identify the kinds of maxims that were flouted and the reasons for flouting maxims. Two different WhatsApp group chats in a long-distance friendship context were analyzed. The WhatsApp groups consist of members from different areas in East Java. By employing qualitative research, the researcher used the theory of the four types of cooperative principle of the maxim by Grice to analyze the context in which the maxim was flouted and to analyze the reasons of the speakers for flouting the maxims. The finding showed that all kinds of flouting maxims were found, except flouting the maxim of quality. Therefore, it can be concluded that some friendship members usually did not obey the maxims for certain reasons, such as to provide humor and to give the information more effectively.